(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The objectives of this study were to determine the strategic stress management plan of three (3) campuses of Batangas State University. The study utilized descriptive evaluative, descriptive comparative and descriptive correlation design. Census samplingwas done in the selection of respondents. The respondents of the study were sixty (60) teachers. Questionnaire was the main instrument in this study. Statistics such as mean, weighted mean and ranking t-testwere utilized. The researcher based it on a specific demographic profile. The respondents strongly agree in the stress management practices in terms of interpersonal practices and physical practices; however, they disagree in intrapersonal practices. Respondents agree behavioral factors, emotional factors and physical factors causes stress to them while they disagree that cognitive factors cause stress to them. The respondents agree that they experienced challenges on the stress management practices. There is no significant difference on the stress management practices when profile is considered. There is no significant difference on the factors that cause stress when profile is considered. There is no significant difference on the challenges experienced on the stress management practices when profile is considered. There is asignificant relationship between stress management practices and factors that cause stress to the respondents. There is a significant relationship between stress management practices and the challenges experienced on it. There is a significant relationship between factors that cause stress to the respondents and the challenges experienced on it. The Stress Management Practices Program isdesigned by the researcher based on the results of the study.